Outbreak of avian botulism and its effect on waterbirds in the Wilderness Lakes, South Africa - Ian A. Russell; Rodney M. Randall; David Zimmerman; Danny Govender (Koedoe: African Protected Area Conservation and Science, 2019)
Avian botulism has been reported in many areas worldwide, particularly in North America, where at times it has resulted in die-offs of hundreds of thousands of waterbirds. By contrast, there are few reported cases in wild waterbird communities in South Africa. Mass die-offs of waterbirds in the Wilderness Lakes, South Africa, were first observed in January 2015, raising concerns about the effect of disease on the status of waterbird communities in this Ramsar site. Surveys of bird carcasses were undertaken between 2015 and 2017. An estimated 1115 individuals from 23 species were affected, with sick individuals displaying symptoms of avian type C, C and D or E botulism. The highest mortality was amongst red-knobbed coot (Fulica cristata), Cape shoveler (Anas smithii) and yellow-billed duck (Anas undulata), respectively comprising 60%, 18% and 9% of affected individuals. Cape shoveler was found to be particularly susceptible to the disease. Deaths occurred mainly during summer and autumn (November–April). No mortalities were recorded amongst 44 waterbird species, of which common moorhen (Gallinula choropus), African purple swamphen (Porphyrio madagascariensis) and reed cormorant (Phalacrocorax africanus) are widespread and abundant. The reasons for the outbreaks remain elusive, as environmental changes characteristic of a botulism outbreak, notably a decline in water level and dissolved oxygen, did not differ substantially from earlier years when no disease outbreaks were observed. The role of fish, and in particular the recently introduced common carp (Cyprinus carpio) in the progression of the disease, remains speculative, although worthy of investigation. The removal of carcasses for disease control should be continued.